The use of oral questioning to improve students’ reasoning skills in primary school mathematics learning - Mahmud, Muhammad Sofwan; Mohd Drus, Nadia Fasha (Frontiers in Education, 2023)
Reasoning skills are essential mathematical skills that need to be taught to students starting in primary school and have even become the main domain in global assessments such as TIMSS and PISA. Therefore, this study aimed to explore the implementation of the use of oral questioning in improving students' reasoning skills in mathematics at the primary school level. Data for the qualitative case study was collected through semi-structured interviews, observations, and field notes. Six mathematics teachers from six different primary schools were selected as participants in the study using the purposive sampling method. The data were then analyzed using a constant comparative method to identify the patterns and themes that emerged from the data obtained. The study found six types of oral questions that are identified as being used by mathematics teachers to help students improve their mathematical reasoning skills and thinking, namely provocative mathematical questions, puzzle-shaped questions, breaking down hard problems into easier parts, contextual questions, questions to explain the mistakes, and questions asking for clarification. The findings showed that primary mathematics teachers could use a variety of oral questions to help the student develop their mathematical reasoning skills and, at the same time, assist them in developing higher-order thinking skills. This research has implications for expanding the literature and understanding of how primary school teachers perceive that using certain oral questions can help improve students' mathematical reasoning. Besides, the study's results revealed the importance of oral questioning in teaching mathematical reasoning skills.